Novel application of ribonucleoprotein-mediated CRISPR-Cas9 gene editing in plant pathogenic oomycete species - Erika N. Dort; Nicolas Feau; Richard C. Hamelin (Microbiology Spectrum)
ABSTRACT CRISPR-Cas9 gene editing has become an important tool for the study of plant pathogens, allowing researchers to functionally characterize specific genes involved in phytopathogenicity, virulence, and fungicide resistance. Protocols for CRISPR-Cas9 gene editing have already been developed for Phytophthoras, an important group of oomycete plant pathogens; however, these efforts have exclusively focused on agricultural pathosystems, with research lacking for forest pathosystems. We sought to develop CRISPR-Cas9 gene editing in two forest pathogenic Phytophthoras, Phytophthora cactorum and P. ramorum, using a plasmid-ribonucleoprotein (RNP) co-transformation approach. Our gene target in both species was the ortholog of PcORP1, which encodes an oxysterol-binding protein that is the target of the fungicide oxathiapiprolin in the agricultural pathogen P. capsici. We delivered liposome complexes, each containing plasmid DNA and CRISPR-Cas9 RNPs, to Phytophthora protoplasts using a polyethylene glycol-mediated transformation protocol. We obtained two ORP1 mutants in P. cactorum but were unable to obtain any mutants in P. ramorum. The two P. cactorum mutants exhibited decreased resistance to oxathiapiprolin, as measured by their radial growth relative to wild-type cultures on oxathiapiprolin-supplemented medium. Our results demonstrate the potential for RNP-mediated CRISPR-Cas9 gene editing in P. cactorum and provide a foundation for future optimization of our protocol in other forest pathogenic Phytophthora species.IMPORTANCECRISPR-Cas9 gene editing has become a valuable tool for characterizing the genetics driving virulence and pathogenicity in plant pathogens. CRISPR-Cas9 protocols are now well-established in several Phytophthora species, an oomycete genus with significant economic and ecological impact globally. These protocols, however, have been developed for agricultural Phytophthora pathogens only; CRISPR-Cas9 systems have not yet been developed for any forest pathogenic Phytophthoras. In this study, we sought to establish CRISPR-Cas9 gene editing in two forest Phytophthora pathogens that cause widespread tree mortality: P. cactorum and P. ramorum. We successfully obtained gene mutations in P. cactorum and demonstrated a decrease in fungicide resistance, a trait that could impact the pathogen’s ability to cause disease. However, the same protocol did not yield any mutants in P. ramorum. The results of our study will serve as a baseline for the development of CRISPR-Cas9 gene editing in forest Phytophthoras and other oomycetes.